Effects on the Post-translational Modification of H3K4Me3, H3K9ac, H3K9Me2, H3K27Me3, and H3K36Me2 Levels in Cerebral Cortex, Hypothalamus and Pons of Rats after a Systemic Administration of Cannabidiol: A Preliminary Study - Pastrana-Trejo, José C.; Duarte-Aké, Fátima; Us-Camas, Rosa; De-la-Peña, Clelia; Parker, Linda; Pertwee, Roger G.; Murillo-Rodríguez, Eric (Central Nervous System Agents in Medicinal Chemistry, 2021)
Background: Cannabidiol (CBD), a non-psychotropic constituent of Cannabis sativa, has shown therapeutic promises by modulating several pathological conditions, including pain, epilepsy autism, among others. However, the molecular mechanism of action of CBD remains unknown and recent data suggest the engagement on CBD´s effects of nuclear elements, such as histone activity. Aim: This study assessed the changes in the post-translational modification (PTM) on the histones H3K4Me3, H3K9ac, H3K9Me2, H3K27Me3, and H3K36Me2 in several brain regions of rats after the administration of CBD (20 mg/Kg/i.p.). Objective: To evaluate the effects on the PTM of histones H3K4Me3, H3K9ac, H3K9Me2, H3K27Me3, and H3K36Me2 levels in the cerebral cortex, hypothalamus and pons of CBD-treated rats. Methods: Ten adult rats were randomly assigned into 2 groups: Control or CBD (20 mg/Kg/i.p). Animals were sacrificed after treatments and brains were collected for dissections of the cerebral cortex, hypothalamus and pons. Samples were analyzed for PTM on the histones H3K4Me3, H3K9ac, H3K9Me2, H3K27Me3, and H3K36Me2 levels by Western blot procedure. Results: CBD increased the PTM levels on the histones H3K4Me3, H3K9ac, and H3K27Me3 in the cerebral cortex whereas no significant differences were found in H3K9Me2 and H3K36Me2. In addition, in the hypothalamus, CBD decreased the contents of H3K9ac while no significant effects were observed in H3K4Me3, H3K9Me2, H3K27Me3, and H3K36Me2. Lastly, in the pons, CBD- treated rats showed a significant decline on the PTM levels of H3K4Me3 whereas no statistical differences were found in H3K9ac, H3K9Me2, H3K27Me3, and H3K36Me2. Conclusion: The study showed that CBD induced differential effects in levels of PTM on the histones H3K4Me3, H3K9ac, H3K9Me2, H3K27Me3, and H3K36Me2 in several brain regions.
Keywords: Cannabidiol